2022
DOI: 10.3390/biomedicines10020411
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Checkpoint Inhibitors in Advanced Bladder Cancer: Seize the Day

Abstract: Background: In advanced bladder cancer (BCa), platinum-based chemotherapy represents the first-choice treatment. In the last ten years, immune checkpoint inhibitors (ICIs) have changed the therapeutic landscape of many solid tumors. Our review aims to summarize the main findings regarding the clinical use of ICIs in advanced BCa. Methods: We searched PubMed, Embase, and Cochrane databases, and conference abstracts from international congresses (ASCO, ESMO, ASCO GU) for clinical trials, focusing on ICIs as mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 86 publications
(172 reference statements)
0
21
0
1
Order By: Relevance
“…Immunosuppressants currently developed for PD-1 and PD-L1 show better prognostic effects than chemotherapy in the second-line treatment of MUC ( 38 ). ICIs targeting CTLA4, such as ipilimumab and tremelimumab, have also proven therapeutic effects in treating advanced BCa ( 39 ). Extracellular matrix disassembly and remodeling can affect tumor invasion by altering the tumor microenvironment ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressants currently developed for PD-1 and PD-L1 show better prognostic effects than chemotherapy in the second-line treatment of MUC ( 38 ). ICIs targeting CTLA4, such as ipilimumab and tremelimumab, have also proven therapeutic effects in treating advanced BCa ( 39 ). Extracellular matrix disassembly and remodeling can affect tumor invasion by altering the tumor microenvironment ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibiting PD-L1 through designing and utilizing specified monoclonal antibodies (mAbs) has been widely brought into play in cancer immunotherapy in recent years. Some of these immune checkpoint inhibitors (ICI) like Durvalumab, Avelumab, and Atezolizumab are FDA-approved ( Table 1 ) ( 51 , 96 , 97 ). A clinical trial study (NCT02639065) of Durvalumab on thirty-seven patients with esophageal cancer showed a relapse-free survival (RFS) rate of 73% ( 98 ).…”
Section: Pd-l1mentioning
confidence: 99%
“…Immunotherapy profoundly transformed the therapeutic scenario of several malignancies; in fact, in the last two decades, the use of immune checkpoint inhibitors (ICIs) spread in many solid tumors after achieving meaningful improvements in survival and quality of life [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Finding predictive biomarkers for ICIs to allow a better patient selection remains one of the most critical unanswered questions in contemporary immune oncology.…”
Section: Introductionmentioning
confidence: 99%